The Role of Study and Work in Cannabis Use and Dependence Trajectories among Young Adult Frequent Cannabis Users - Liebregts, Nienke; van der Pol, Peggy; de Graaf, Ron; Van Laar, Margriet; van den Brink, Wim; Korf, Dirk J. (Frontiers in Psychiatry, 2013)
Life course theory considers events in study and work as potential turning points in deviance, including illicit drug use. This qualitative study explores the role of occupational life in cannabis use and dependence in young adults. Two and three years after the initial structured interview, 47 at baseline frequent cannabis users were interviewed in-depth about the dynamics underlying changes in their cannabis use and dependence. Overall, cannabis use and dependence declined, including interviewees who quit using cannabis completely, in particular with students, both during their study and after they got employed. Life course theory appeared to be a useful framework to explore how and why occupational life is related to cannabis use and dependence over time. Our study showed that life events in this realm are rather common in young adults and can have a strong impact on cannabis use. While sometimes changes in use are temporary, turning points can evolve from changes in educational and employment situations; an effect that seems to be related to the consequences of these changes in terms of amount of leisure time and agency (i.e. feelings of being in control).